ANALISIS PENGGUNAAN INFORMASI AKUNTANSI DAN INFORMASI NON AKUNTANSI DALAM KEPUTUSAN PEMBERIAN FASILITAS KREDIT PADA PT. BANK MANDIRI (PERSERO) Tbk AREA MANADO - Niode, Marshella Patricia; Saerang, David P.E.; Ilat, Ventje (ACCOUNTABILITY, 2016)
One of the efforts that the bank made to anticipate and minimize the credit risk is already started since the applicant proposed the loan. This thing is done by analyze all sort of the information from the applicant. Loan giver must do a deep analyze to sorts of information due to the giving of the right decision of loan, and by that for, to analyze the loan proposal of the applicant, the bank needs the accounting information in the form of financial statement or in the other form along with non-accounting information from the applicant that’s both historical as well as contemporary, or future. The purpose of this study was to analyze the use of accounting information in the decision to grant credit facilities and to analyze the use of non-accounting information in the decision to grant credit facilities. The object of this research is PT. Bank Mandiri (Persero) Tbk Area Manado. The instrument in this research is questionares and interview. Analysis method that used is the deskriptive analysis. The result of the research is that the accounting information and non-accounting information is needed to determine the distribution of loan properly given to debitor in the concerned to reduced the non performing loan (NPL) in the PT. Bank Mandiri (Persero) Tbk. Keywords: Accounting Information, Non-Accounting Information, Decision of Loan Facilities.